Acute toxicity of Dichlorovos and Monocrotophos and their effect on respiratory metabolism of Macrobrachium malcolmsonii. - Venugopal, G; Narasimhacharyulu, V; Venkateshvaran, K (Indian Journal of Fisheries, 2011)
Acute toxicity of two organophosphorous pesticides, dichlorovos andmonocrotophos were evaluated for Macrobrachium malcolmsonii. It was foundthat dichlorovos was more toxic than monocrotophos. M. malcolmsonii showedsignificant changes in the rate of respiration on exposure to lethal and sub lethalconcentration. The LC50 values predict potential hazard that exist to prawnfishery particularly in polyculture grow out practices.